New species and a new subgenus of Spirorbinae (Serpulidae: Polychaeta) from Kenya - Knight-Jones, P. (J. Zool. Lond., 1972)
Four species were collected, all attached to marine angiosperms, Pileolaria daijonesi sp.n. being the most abundant. The other three have the collar folds fused dorsally, as is characteristic of Dexiospira (=Neodexiospira Pillai), which is here regarded as a subgenus of Janua. Janua (Dexiospira) formosa (Bush) and Janua (Dexiospira) steueri Sterzinger are distinguished clearly from one another for the first time and shown to be widely distributed in warm seas. Janua (Fauveldora) kayi subgen. et sp.n. is a very closely related sinistral form, which extends to the Persian Gulf and Ceylon. Reviewing serpulids, it seems that the primitive position of the operculum in Serpulinae and Spirorbinae was sinistral. The most recent changes involving this character, however, have been situs inversus back-mutations, from stocks which are dextral and presumably more labile.